Spatiotemporal analysis of ecosystem services and the impact of new-type urbanization: A case study of Chengdu, China - Pinjian Li; Tianhong Li (Ecological Indicators)
A comprehensive understanding of the dynamics of ecosystem services (ESs) and their relationships with new-type urbanization is crucial for promoting sustainable development, particularly in rapidly urbanizing areas. This study employed Chengdu, a rapidly urbanizing city, as the study area to investigate the spatiotemporal variation characteristics of ESs and the impact of new-type urbanization on ESs from 2000 to 2020. The results revealed that the ESs in Chengdu underwent significant changes during the study period. An increase was observed in water yield (WY) and habitat quality (HQ), while food supply (FS) and soil retention (SR) showed mixed trends. Carbon sequestration (CS) and water purification (WP) remained relatively stable. The majority of ESs, including FS, SR, CS, WP and HQ, exhibited synergistic relationships. A comprehensive assessment system encompassing population, economy and environment urbanization revealed a continuous improvement in the level of new-type urbanization in Chengdu. The new-type urbanization factors were generally found to be negatively correlated with ESs, with environmental urbanization making a greater contribution. Four ecosystem service bundles were identified at the watershed scale, including City Construction Bundle, Supply and Sustain Bundle, Transition Management Bundle, and Ecological Protection Bundle. Therefore, this study underscores the critical need to balance new-type urbanization development and ESs, and also provides support for targeted urban management in Chengdu, as well as other rapidly urbanizing cities.